2019
DOI: 10.1159/000500048
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Preterm Birth following Open Fetal Myelomeningocele Repair: Results from a Prospective Cohort

Abstract: <b><i>Background:</i></b> Fetal myelomeningocele (fMMC) repair is a therapeutic option in selected cases. This study aimed to identify risk factors for preterm birth (PTB) following open fMMC repair. <b><i>Methods:</i></b> Sixty-seven women underwent fMMC repair and delivered a baby between 2010 and 2018 at our center. Demographic, surgical, and pregnancy complications, including potential risk factors for PTB such as preterm premature rupture of membranes (PPROM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…The remaining 112 were assessed for eligibility by full-text reading. The selection left us with 27 eligible articles that were included in the study ( Figure 1 ) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining 112 were assessed for eligibility by full-text reading. The selection left us with 27 eligible articles that were included in the study ( Figure 1 ) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes the maternal outcomes after prenatal interventions as reported in different studies. Two studies with early experience (defined as less than 30 patients) reported placental abruption rates of 10% [ 28 ] and 0% [ 23 ] whereas studies including more than 30 patients reported an average rate of placental abruption of 5.9% [ 17 , 19 , 24 , 25 ]. Only two studies, both having late experience, reported pulmonary edema rates of 2% [ 24 ] and 2.98% [ 17 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations